Efficacy of Plastic Waste Strips Towards Enhancement of Shear Capacity of Reinforced Concrete Beams - Muhammed, Sabah Hashim; Jadooe, Awad; AL-Khafaji, Ali Ghanim A.; Al Maimuri, Najah M. L. (Civil Engineering Journal, 2025)
The amount of plastic waste produced worldwide has been steadily rising. Manufacturing processes, service industries, and municipal solid waste produce a significant amount of waste plastic. One common construction and industrial waste that could be employed as shear reinforcement in concrete beams for specified purposes is the plastic waste strips, since they have relatively high tensile strength. Such plastic strips are used to tie clay bricks, floor finishing tiles, walkway finishing blocks, curbstones, and so on in different industrial products. This study examines an approach that uses plastic waste strips in place of conventional stirrups to enhance the shear performance of reinforced concrete (RC) beams. A set of shear tests was performed on carefully constructed 150 mm width × 225 mm depth × 1400 mm length beam specimens to evaluate failure mechanisms, modes of failure, crack patterns, and shear strength. All beams have the same flexural requirements, so they were ensured to fail by exceeding their shear strength under the applied load. This study examined five concrete beams that were reinforced internally using plastic waste strips in the shear region, as well as one control beam. The tested beams were reinforced using various strip spacings and configurations. The results of the tests indicated that increasing the plastic waste strips improved the concrete section shear strength. As the number of plastic strips in the section increases, the distance between each strip is drastically reduced, increasing the shear capacity of the beam. The experimental results indicate that the beam with six vertical plastic waste strips in its section has a 75% higher shear strength capacity than the reference beam without any transverse reinforcement. In addition, shear resistance is higher in the beam with plastic strips at 45° and 135° inclined angles than in the beam with vertical plastic strips in the same amount of plastic strips. Based on these findings, reinforced concrete beams can be utilized for specific purposes by employing plastic waste strips as transverse reinforcement to resist internal shear forces.